2008
DOI: 10.1063/1.2920764
|View full text |Cite
|
Sign up to set email alerts
|

Mid-IR focal plane array based on type-II InAs∕GaSb strain layer superlattice detector with nBn design

Abstract: A midwave infrared camera ͑ c = 4.2 m͒ with a 320ϫ 256 focal plane array ͑FPA͒ based on type-II InAs/ GaSb strain layer superlattice ͑SLs͒ has been demonstrated. The detectors consist of an nBn heterostructure, wherein the SL absorber and contact layers are separated by a Al 0.2 Ga 0.8 Sb barrier layer, which is designed to have a minimum valence band offset. Unlike a PN junction, the size of the device is not defined by a mesa etch but confined by the lateral diffusion length of minority carriers. At 77 K, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…The measurement speed on the other hand is currently limited to 30 nm/min due to the monochromator scanning and long integration time needed to improve the signal-to-noise ratio. This could be significantly reduced by using a spectrometer with a detector array 17 .…”
mentioning
confidence: 99%
“…The measurement speed on the other hand is currently limited to 30 nm/min due to the monochromator scanning and long integration time needed to improve the signal-to-noise ratio. This could be significantly reduced by using a spectrometer with a detector array 17 .…”
mentioning
confidence: 99%
“…Recently, an MWIR focal plane array based on an unpassivated nBn structure with an AlGaSb barrier and an InAs/GaSb T2SL n-type absorber has been reported. 18 In this paper, we demonstrate LWIR nBn photodetectors with an InAs/InAsSb T2SL absorber having a cutoff wavelength of 13.2 lm. The designed nBn device is grown on a Te-doped (100) 2 in.…”
mentioning
confidence: 99%
“…Figure 2a Our electrical measurements showed that Al 2 O 3 is a better alternative for SiO x passivation. The significant reduction in dark current and increase in dynamic resistance due to ALD deposited Al 2 O 3 passivation is very encouraging for use in FPA applications [9,16,17]. The inverse of the dynamic resistance area product at zero bias as a function of the perimeter to area ratio at 77K for passivated and unpassivated detectors are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…shows periodic structure of the p-i-n design superlattice crystal with corresponding thicknesses and doping concentrations. It starts with 100 nm thick GaSb buffer layer and 20 nm Al (x) GaAs (y) Sb as an insulator and etch stop layer, followed by 1000 nm GaSb:Be (p=1.0x10 17 Figure 1b shows device structure of the p-i-n photodiode. 200 cycles Al 2 O 3 passivation layer deposition carried out in atomic layer deposition system (Cambridge Nanotech Savannah 100) with 150 C o as the substrate holder temperature.…”
Section: Methodsmentioning
confidence: 99%